Determination of Risk Areas in the Cimahi City (Drainage Sector) Based on City Sanitation Strategy Guidelines - Iwan Juwana; Elvira Rizqita Utami (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
Cimahi is one of the cities which participated in the Accelerated Habitat Sanitation Development Program in 2011 due to its poor sanitation conditions. The city experienced high flooding in 2018 as observed in the 36.4 hectares or approximately 0.76% of the total area affected even though its drainage system was discovered to be covering 89.87% in 2015. There are also several reports of displacement of residents and significant financial loss in the city due to flooding in the past decade and this means urgent attention needs to be provided to improve the condition of the city. Therefore, this study was conducted to calculate the level of risk from the drainage sector in each urban village of Cimahi City. This involves using scores ranging from 1 – 4, with a score of 1 indicating very low risk while 4 represents very high risk based on exposure factors such as percentage of inundation area, sanitation risk index (IRS) score, and the opinions of local government as well as impact factors such as population, population density, poverty rate, and urban/rural function. The research made use of both primary and secondary data with the primary data obtained through interviews with the population in the study area and local government representatives while secondary data were obtained from different institutions. The results showed 7 out of the 16 urban villages in Cimahi City are in Risk Category 1, 5 in Category 2, 1 in Category 3, and the remaining 2 in Category 4. This information with the risk category map for each village is expected to be used by the local government of Cimahi to analyze the flood-related problems better and create more effective solutions.